Mitigating Agricultural Greenhouse Gas Emissions: A Review of Scientific Information for Food System Planning - Tara L. Moreau; Jennie Moore; Kent Mullinix (Journal of Agriculture, Food Systems, and Community Development, 2016)
Agriculture contributes significantly to anthropogenic greenhouse gases (GHGs), with estimates of agriculture's contribution ranging from 10% to 25% of total global GHG emissions per year. The science regarding mitigating (reducing and removing) GHGs through agriculture is conflicting and inconclusive. However, the severity and urgency of climate change and its potential effects on food security demonstrate that we must include mitigation within food system planning frameworks. In British Columbia, Canada, the provincial government has established significant GHG reduction targets for its agencies, and has called on local governments to reduce their carbon footprints through a charter and incentive, as well as through growth management legislation. At the same time, local governments, are giving increased attention to development of local/regional agri-food systems. However, GHG mitigation efforts do not yet seem to factor into local agri-food system discussions. Although frameworks for reporting agriculture GHGs exist, local government measurement of agriculture mitigation is hampered by a lack of agriculture GHG inventories, limited data availability, and the inherent variability in agriculture emissions and removals due to the dynamic nature of farm ecosystems. With the goal of informing local governments and food system planners on the importance of agriculture GHG mitigation, this paper (1) reviews the science of GHGs, (2) describes sources of agriculture GHG emissions and illustrates potential mitigation practices, (3) discusses the variability of agriculture mitigation science, (4) highlights the importance of agriculture GHG inventories, and (5) emphasizes the necessity for local agriculture mitigation strategies.